A Comprehensive Evaluation of Sdox, a Promising H2S-Releasing Doxorubicin for the Treatment of Chemoresistant Tumors - Alov, Petko; Al Sharif, Merilin; Aluani, Denitsa; Chegaev, Konstantin; Dinic, Jelena; Divac Rankov, Aleksandra; Fernandes, Miguel X.; Fusi, Fabio; García-Sosa, Alfonso T.; Juvonen, Risto; Kondeva-Burdina, Magdalena; Padrón, José M.; et al. (Frontiers in Pharmacology, 2022)
Sdox is a hydrogen sulfide (H2S)-releasing doxorubicin effective in P-glycoprotein-overexpressing/doxorubicin-resistant tumor models, and not cytotoxic, as the parental drug, in H9c2 cardiomyocytes. Aim of this study was the assessment of Sdox drug-like features as well as, its absorption, distribution, metabolism and excretion (ADME)/toxicity properties, by a multi- and transdisciplinary in silico, in vitro, and in vivo approach. Doxorubicin was used as the reference compound. The in silico profiling suggested that Sdox possesses higher lipophilicity and lower solubility compared to doxorubicin and the off-targets prediction revealed relevant differences between Dox and Sdox towards several cancer targets, suggesting different toxicological profiles. In vitro data showed that Sdox is a substrate with lower affinity for P-glycoprotein, less hepatotoxic, and causing less oxidative damage than doxorubicin. Both anthracyclines inhibited CYP3A4, but not hERG currents. Unlike doxorubicin, the percentage of zebrafish live embryos at 72 hpf were not affected by Sdox treatment. In conclusion, these findings demonstrate that Sdox displays a more favorable drug-like ADME/toxicity profile than doxorubicin, different selectivity towards cancer targets along with a greater preclinical efficacy in resistant tumors. Therefore, Sdox represents a prototype of innovative anthracyclines, worth of further investigations in clinical settings.